2017
DOI: 10.1108/sd-06-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Live long and prosper: the search for business longevity

Abstract: Purpose This paper aims to discuss key aspects of the longevity of business enterprises across the world. It explores the parameters that set apart a company which had survived for more than 1,400 years from most large companies which survive for a fraction of this time. Design/methodology/approach The paper integrates observations from two important research papers on the topic, and from the author’s own research. Findings Contrary to expectations, long-surviving firms are usually conservative about chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…With respect to the elements that enable a firm to sustain longer, the literature is contradictory. For instance, K. R. Sharma and Dixit (2017), while investigating the longevity of century-old firms identified five keys to the longevity of such firms: be conservative, be rooted, diversify sensibly, compete but also cooperate, and look back. To some extent, these aspects seem contrary and conservative to the established findings in the existing literature that suggest adaptation (Hatum & Pettigrew, 2004), fast learning, and timely response to environmental changes (Pishdad & Haider, 2013) and customers' needs (E. W. Anderson, Fornell, & Lehmann, 1994).…”
Section: Definition Of Cslmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the elements that enable a firm to sustain longer, the literature is contradictory. For instance, K. R. Sharma and Dixit (2017), while investigating the longevity of century-old firms identified five keys to the longevity of such firms: be conservative, be rooted, diversify sensibly, compete but also cooperate, and look back. To some extent, these aspects seem contrary and conservative to the established findings in the existing literature that suggest adaptation (Hatum & Pettigrew, 2004), fast learning, and timely response to environmental changes (Pishdad & Haider, 2013) and customers' needs (E. W. Anderson, Fornell, & Lehmann, 1994).…”
Section: Definition Of Cslmentioning
confidence: 99%
“…Though CSL is a related concept, it is primarily different from "longevity" because it addresses the "ability" of a firm to sustain its longevity beyond average firm age. Some studies have partly contributed toward the conceptualization of CSL (Ibrahim, McGuire, & Soufani, 2009;Napolitano et al, 2015; K. R. Sharma & Dixit, 2017) and a few others have partly contributed to its operationalization (Fahed-Sreih & Djoundourian, 2006;Fatoki, 2013). However, these studies are neither converging toward a common concept nor are they thorough enough to incorporate all aspects of CSL.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study extends the general knowledge on the digitalisation of long-lived firms that has been proposed in the literature (e.g. Hicks and Hegde, 2005; Sebastian et al , 2017; Sharma and Dixit, 2017; Erdogan et al , 2019) by highlighting actions, conditions and effects of digitalisation for the long-lived firms’ development and providing empirical evidence on how these activities can be carried out by the firms themselves.…”
Section: Discussionmentioning
confidence: 58%
“…As regards innovation to support the digital transformation process in long-lived firms, scholars have tended to define the minimum threshold for company longevity as 100 years of continuous activity. Sharma and Dixit (2017, p. 1), in particular, analysing key factors for longevity in a detailed Japanese case study, observed that it is very important for this kind of firm to be conservative, asserting that “the pressure to exploit newer opportunities and invest resources to ward off potential threats is high, particularly in the digital era. However, long-established firms are known to stay true to their core values and principles and usher in large-scale radical changes very selectively”.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation